2023
DOI: 10.3399/bjgp.2023.0103
|View full text |Cite
|
Sign up to set email alerts
|

Dementia prevention and the GP’s role: a qualitative interview study

Danielle Jones,
Rachael Drewery,
Karen Windle
et al.

Abstract: Background: General Practitioners (GPs) play an increasingly important role in proactively preventing dementia. 40% of dementia cases could be prevented or delayed by targeting 12 modifiable risk factors throughout life. However, little is known about how GPs perceive their role in dementia prevention and associated barriers. Aims:To explore the role of GPs in dementia prevention. Design and Setting: A qualitative study among UK GPs. Method: Semi-structured online interviews with 11 UK GPs exploring their view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…They also agreed that it would be of added value to mention brain health in their role as health advisor. Indeed, findings from a qualitative study in general practitioners (GPs) from the United Kingdom also highlighted that GPs consider dementia risk reduction to fall within their scope [ 45 ]. Guidelines on how this can be done have been published [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also agreed that it would be of added value to mention brain health in their role as health advisor. Indeed, findings from a qualitative study in general practitioners (GPs) from the United Kingdom also highlighted that GPs consider dementia risk reduction to fall within their scope [ 45 ]. Guidelines on how this can be done have been published [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are certain potential barriers that should be considered. Limited time and resources being the major ones, that may force PCPs to neglect efforts towards prevention, despite their intentions, as it is usually less of priority or urgent [ 45, 46 ]. Dutch general practitioners for example do not get reimbursed for dedicating time towards discussing prevention with their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read Jones and colleagues' paper on the role of GPs in dementia prevention with great interest. 1 While the research introduces a novel strategy for addressing this challenge and acknowledges barriers to communicating dementia risk such as time, there are some notable absences.…”
Section: Re-thinking the Role Of Primary Care In Dementia Preventionmentioning
confidence: 99%
“…Surveys of healthcare professionals have found that they have a low awareness of dementia risk factors 3. And a recent—albeit small—qualitative study suggested that UK GPs don’t widely discuss dementia risk with their patients, even when their circumstances or lifestyles put them at increased risk 4. This includes having conditions like hypertension, which affects 16 million adults in the UK, many of whom successfully self-manage it 5…”
mentioning
confidence: 99%